From city to Learning City ̶ The involvement of stakeholders in Lucca and Trieste - Biagi, Giulia (Tudásmenedzsment, 2022)
This paper will elaborate upon the model of the Italian Learning City of Lucca and Trieste, recently entered in the Global Network of the Learning Cities of the UNESCO Institute for Lifelong Learning. In a learning city citizens and institutions must participate to achieve global goals and the mission of the SDGs 2030 Agenda and lifelong learning objectives. Regarding the construction of a learning city the UNESCO UIL has given guidelines and best practices to help this transformation, which manifest as a unique process in every city. Through the Italian policies on adult education and the local administrative decentralization has been possible the integration of the UNESCO learning city model with the experiences of Lucca and Trieste on national territory. The involvement of stakeholders is a fundamental step to transform the city, in a city that learns. The actors involved included a wide variety of subjects like civil society, schools and businesses. The question aims to answer how it is built and implemented in a learning city or smart city the stakeholders’ network. The hypothesis is that through the comparison of Lucca and Trieste, the best practices produced will emerge. The data are interpreted through: main goals of the learning cities, issues in the community learning activities, barriers of collaboration of stakeholders, forms of collecting and sharing knowledge in the city. Taking into account the UNESCO UIL guidelines. Every learning city needs participation involving all stakeholders and to include all citizens facing challenges at many levels. It will therefore be essential for administrations to reduce the barriers to participation, meet the needs of its population and create learning events to share and acquire knowledge.